Trifunktionelle Cyclopropane als Vorstufen von Triafulven und Calicen - Andreas Weber; Gabriele Sabbioni; Roberto Galli; Markus Neuenschwander (CHIMIA)
A series of 1,1-dihalo-2-X-cyclopropanes 3 have been prepared and characterised. Cyclopropanes of type 3 could be of interest as starting materials with respect to the attempted synthesis of triafulvene and calicene.